TRANSFORMASI GOOD FAITH PRINCIPLE DALAM HUKUM PERBANKAN KHUSUSNYA BPR: PERSPEKTIF LOKAL NASIONAL DAN INTERNASIONAL - Retno Murni; Ni Ketut Supasti Dharmawan; Putu Aras Samsithawrati (Arena Hukum, 2018)
AbstractThe Good faith principle as stated in Article 1338 paragraph (3) of the Civil Code, has not been maximally implemented in BPR credit agreements, so it is important to review the transformation of good faith principle of the Civil Code in banking provisions, especially BPR in realizing sound credit. The research uses normative juridical legal methods. The results of the study show that the transformation of the principle of good faith stated in the Civil Code has not been explicitly stated in the provisions of banking law in Indonesia. The existence of principle of good faith explicitly only exists in Article 1338 Paragraph (3) of the Civil Code. Meanwhile, in the provisions of the Banking Law the existence of the principle of good faith is only implied by the principle of economic democracy by using the precautionary principle that is applied carefully and in good faith, as well as the principles of trust and confidence in good ability, ability, intention and morals from customers or the community in returning credit. The transformation of the principle of good faith should be clearly stated in the norm structure into the Banking Law and other related banking legal provisions.AbstrakGood faith principle sebagaimana tercantum pada Pasal 1338 ayat (3) KUHPerdata, belum diimplementasikan secara maksimal dalam perjanjian kredit BPR, sehingga penting mengkaji transformasi asas itikad baik KUH Perdata dalam ketentuan perbankan khususnya BPR dalam mewujudkan perkreditan yang sehat. Metode penelitian menggunakan metode penelitian hukum yuridis normatif. Hasil penelitian menunjukkan bahwa Transformasi asas itikad baik yang tercantum dalam KUHPerdata belum secara eksplisit ternormakan dalam ketentuan hukum perbankan di Indonesia. Keberadaan asas Itikad baik secara eksplisit hanya eksis dalam Pasal 1338 Ayat (3) KUHPerdata. Sementara itu, dalam ketentuan Undang-Undang Perbankan keberadaan asas itikad baik hanya tersirat dari asas demokrasi ekonomi dengan menggunakan prinsip kehati-hatian yang diterapkan secara hati-hati dan itikad baik, serta prinsip kepercayaan dan keyakinan akan kemampuan, kesanggupan, itikad serta akhlak yang baik dari nasabah atau masyarakat dalam mengembalikan kredit. Transformasi asas itikad baik sebaiknya dituangkan dalam struktur norma secara tegas ke dalam Undang-Undang Perbankan dan ketentuan hukum perbankan terkait lainnya.